Surviving acute aortic dissection: one nurse's mission to guide and support patients on their daunting journey. (2nd March 2022) - Hope, Emma
Abstract : As the specialist nursing roles within the cardiac sphere become increasingly diverse, Emma Hope provides some insight into the role of an aortic specialist nurse and the patient journey with acute aortic dissection.